2. IMPLEMENTATION RESULTS AND IMPACT OF THE ZERO-COVID STRATEGY IN THE COVID-19 PANDEMIC: A SCOPING REVIEW (Vietnam Journal of Community Medicine, 2023)
Objectives: Describe the advantages and impacts of the Zero-COVID strategy. Method: The search strategy includes terms related to (1) Zero-COVID and (2) COVID-19 in PubMed/MEDLINE, and Science Direct. Original research papers on the advantages and impacts of the Zero-COVID strategy in English were selected for the study. Data from selected studies were extracted and classified into themes and topics. The PRISMA principles were used to perform a scoping evaluation of several medical databases. Results: In total, this research includes nine studies. The Zero-Covid strategy has brought some positive impacts, including significantly reducing morbidity, mortality, and environmental pollution. However, the Zero-Covid strategy also brought certain restrictions, which had negative effects on mental health, job loss, and reduced income. Conclusion: While the strategy achieved its healthcare and national security objectives to a certain extent, it also led to substantial and unpredictable social and economic repercussions. The long-term effects on GDP and education remain uncertain. This scoping review can help governments consider preventative measures should the COVID-19 pandemic return.
Keywords: Zero-COVID strategy, benefits, unwanted, COVID-19.